Persistence and fading of the cognitive and socio-emotional benefits of preschool education in a low-resource setting: Group differences and dose-dependent associations in longitudinal data from Vietnam - Dinh, Phuong Thi Thu; Robinson, Julie Ann (Frontiers in Psychology, 2023)
Four analytic approaches examined the effectiveness of preschool education delivered at scale in a resource-limited country. The Young Lives Study in Vietnam provided longitudinal data on children’s receptive vocabulary, mathematics, and life satisfaction at 5, 8, 12 and 15 years of age, and on their self-concept and relationships at 12 and 15 years. In Vietnam, national curricula and teaching standards for preschools and schools, very high levels of preschool attendance, and fee subsidies for disadvantaged children limit the heterogeneity in children’s experiences that can obscure patterns in outcomes. The first analysis found that children who attended preschool (n = 1,562 at 5 years of age) had larger vocabularies at 5, 8, 12 and 15 years, greater mathematics knowledge at 5, 8, and 12 years, and higher life satisfaction at 5 and 12 years of age than the small number of children who did not attend preschool (n = 164 at 5 years of age). The second, found that dose of preschool education (hours per week x 4 x months of attendance) was positively associated with receptive vocabulary and mathematics scores at 5, 8, 12 and 15 years of age, and with life satisfaction at 5 and 15 years of age among children who attended preschool. Although the magnitude of the effect on vocabulary declined over time, it remained stable for mathematics. The third analysis found that a high dose of preschool education allowed disadvantaged rural children to achieve comparable or better scores than their urban peers for receptive vocabulary at 8, 12 and 15 years, mathematics at 12 years, and life satisfaction at all ages. The final analysis found that even a low dose of preschool education improved rural children’s receptive vocabulary at 5, 8 and 15 years, and their numeracy/mathematics scores at 5, 8 and 12 years. Together, the results suggest that preschool attendance had a small but meaningful positive association with Vietnamese children’s cognitive skills and life satisfaction that persisted for at least 10 years. These findings provide insights into the scale, scope, and longevity of effects that can be achieved from scaled-up preschool programs under resource-constrained conditions.